Pengaruh Zakat Produktif terhadap Pengentasan Kemiskinan di Indonesia 1995 - 2023 - Saessatya, Zarel; Atmanti, Hastarini Dwi (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2025)
This study examines the empirical relationship between productive zakat and poverty alleviation in Indonesia, utilising the Autoregressive Distributed Lag (ARDL) approach over the period 1995-2023. The research utilises comprehensive time series data from the National Zakat Board (BAZNAS) and the Central Statistics Agency (BPS) to examine both the short-run and long-run dynamics of zakat's effectiveness in reducing poverty. Augmented Dickey-Fuller tests confirm the stationarity of all variables at the I(0) level. At the same time, the Bounds Test reveals a strong cointegration relationship, with an F-statistic of 6.965159, which significantly exceeds the critical values at all significance levels. The findings demonstrate that productive zakat exhibits significant poverty reduction effects, with a long-run coefficient of -0.454382 (p = 0.0559) and a more substantial short-run impact, as indicated by the first lag coefficient of -0.607590 (p = 0.0180). The Error Correction Model validates the adjustment mechanism toward long-run equilibrium, indicating that zakat serves as both a sustainable redistributive instrument and a short-term economic stabiliser. The model achieves exceptional explanatory power, with an R-squared of 98.97%. The CUSUM test confirms parameter stability across nearly three decades, despite various economic shocks, including the 1997-1998 Asian financial crisis. The results provide robust empirical evidence for integrating zakat into Indonesia's national poverty alleviation strategy, demonstrating its effectiveness as both a counter-cyclical policy tool and a structural mechanism for poverty reduction. The study makes a significant contribution to the Islamic fiscal policy literature by quantifying the measurable economic impact of zakat through rigorous econometric methodology. Based on these findings, this study recommends that productive zakat be more systematically integrated into national poverty alleviation policies by strengthening zakat management institutions, increasing productive zakat allocations oriented towards empowering the mustahik (recipients), and synchronizing zakat programs with government fiscal and social protection policies. Furthermore, increasing transparency, accountability, and utilizing integrated data between zakat institutions and government agencies is crucial to maximizing the impact of zakat as a countercyclical policy instrument and a structural mechanism for sustainable poverty reduction. This study makes a significant contribution to the Islamic fiscal policy literature by quantifying the economic impact of zakat through a rigorous econometric methodology.